Avaliação da relação capacidade-regularização em reservatórios da Bacia do Rio Jaguaribe e na utilização do"paradigma 2VA” - Braga, Tácio Ribeiro (2019)
Due to the unfavorable geological conditions for the extraction of groundwater from the state of Ceará, the main source of supply in the region comes from water withdrawn from artificial reservoirs. Because of the semi-arid climate, which causes huge evaporation rates and the occurrence of intermittent rivers, simpler design methodologies, such as empirical methodologies such as the Rippl Diagram, widely used in the rest of the world, are not accurate to estimate yield in semi-arid climates. For these reasons, the Jaguaribe River basin is one of the most sensitive regions in the world and in need of hydrological studies to improve the techniques for designing reservoirs with lower uncertainties. In this sense, SIMRES appears as a computational tool of reservoir simulation that calculates yield, losses by spill and evaporation using a stochastic approach. In this work, whose objective is to provide more information about the behavior of regularized flows by reservoirs, we used synthetic flow series generated from frequency distribution Gamma II in historical series of fluviometric stations at annual level and at monthly level was used the Method ofFragments. Each synthetic series was simulated with different types of dams that varied its characteristics between: shape of the basin, volume of the reservoir and guarantee of flow. A pre-sizing formula was then determined that estimates the yield at dams in the Jaguaribe basin.